2018
DOI: 10.1111/1346-8138.14634
|View full text |Cite
|
Sign up to set email alerts
|

Open‐label pilot study to evaluate the effectiveness of topical bimatoprost on rhododendrol‐induced refractory leukoderma

Abstract: Rhododendrol (RD), 4‐(4‐hydroxyphenyl)‐2‐butanol, inhibits melanin synthesis and had been used in skin‐whitening cosmetic products until 2013. However, some individuals developed leukoderma on the skin where RD had been applied and have suffered from refractory depigmentation even after discontinuing RD application. Bimatoprost is a prostaglandin F2α analog and is often used for eyelash growth for cosmetic reasons as well as in the treatment of glaucoma. It was reported that bimatoprost induced skin pigmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, it is difficult to draw a conclusion about the effectiveness of bimatoprost on RD-induced leukoderma based on a single case. As described previously (13), the area of skin affected was not measured, since the shape of the leukoderma was complex and it was on the neck of our patient. The surface of the leukoderma was uneven and difficult to measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is difficult to draw a conclusion about the effectiveness of bimatoprost on RD-induced leukoderma based on a single case. As described previously (13), the area of skin affected was not measured, since the shape of the leukoderma was complex and it was on the neck of our patient. The surface of the leukoderma was uneven and difficult to measure.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was enrolled in the previous pilot study to evaluate the effectiveness of bimatoprost on refractory RD-induced leukoderma in November 2016 at the age of 45 years (patient number RD-07), and applied bimatoprost on leukoderma on the left side of the neck once daily for 3 months, and then twice daily for another 3 months. The method is described in detail in the previous paper (13). The area of leukoderma on her neck, which was treated with bimatoprost, reduced in size significantly ( Fig.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Fukaya et al 14 was effective continued with a long-term application for another year and exhibited sustained improvement. 15 Additionally, a clinical study 16,17 demonstrated the benefits of topical prostaglandin derivatives in vitiligo.…”
Section: Topical Agentsmentioning
confidence: 95%
“…Fukaya et al 14 reported the results of an open‐label pilot study investigating topical bimatoprost, a prostaglandin derivative, as a novel therapy. Reportedly, the application of 0.03% bimatoprost solution in patients with intractable RDL remaining on the neck or back of the hands, for 6 months resulted in a marginal improvement in four out of ten patients.…”
Section: Clinical Findings and Treatmentmentioning
confidence: 99%